(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Do bus drivers’ lifestyles affect the occurrence of health problems and absenteeism? Purpose: The purpose of the study was to determine whether the lifestyle of professional bus drivers affects the occurrence of health problems and the phenomenon of absenteeism. Method: A quantitative research method was used in the research. Data were collected using a structured questionnaire, on a sample of 230 professional bus drivers from different bus transport companies in Slovenia. Selected data were analyzed with chi-square test and multiple regression analysis. Results: We determined that there is a relationship between the state of health of professional bus drivers and participation in sport activity and that there is a statistically significant impact of lifestyle on the absenteeism of professional bus drivers. Organization: The study points to the necessity of management’s awareness to improve the conditions for the health status of employees and, consequently, absenteeism. Managers need to be more vigilant in ensuring conditions and social security that will allow employees a higher quality lifestyle. Society: The poor quality lifestyle of professional bus drivers, which includes different addictions, inadequate physical activity, and poor working conditions, is a significant factor causing absenteeism. All these factors influence the onset of negative consequences, such as the direct cost of compensation payments, costs of replacing the absent person, a reduction in productivity, which in turn affect economic growth and the high cost of health care. Originality: This is the first focus group study of professional bus drivers that targets lifestyle and its connection to absenteeism. Limitations/Future Research: The main limitation of the study is the number of respondents. The reason for this is that professional drivers are less responsive in the survey and that the study was conducted only in Slovenia, country of two million people.